2009
DOI: 10.2136/sssaj2008.0153
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous Nitrogen Losses from a Cambisol Cropped to Spring Wheat with Urea Sizes and Placement Depths

Abstract: Globally identifying mitigation options for the emission of reactive N gases from agricultural soils is a research priority. We investigated the effect of urea size and placement depth on sources and emissions of N gases from a Cambisol cropped to spring wheat (Triticum aestivum L.). In Exp. 1, wheat received either prilled urea (PU) mixed within the soil, urea super granule (USG; diam. 10.1 mm) point‐placed at a soil‐depth of 7.5 cm, or no N fertilizer. In Exp. 2, wheat received either USG (diam. 10.2 mm) poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
2
23
0
1
Order By: Relevance
“…But, we also found that nitrogen deep placement significantly decreased cumulative NH 3 losses during the rice growing seasons ( Table 2). The reduction under nitrogen deep placement was also reported in other studies of crop fields (Drury et al, 2006;Liu et al, 2006;Khalil et al, 2009). After basal nitrogen was deep placed, lower soil urease activity was observed under nitrogen deep placement treatments than under S treatment (Table 3), which may lead to less NH 4 + in the soils and floodwater from hydrolyzed nitrogen fertilizers under nitrogen deep placement treatments (Fig.…”
Section: Inhibition Of Nh 3 Volatilization Under Nitrogen Deep Placementsupporting
confidence: 84%
“…But, we also found that nitrogen deep placement significantly decreased cumulative NH 3 losses during the rice growing seasons ( Table 2). The reduction under nitrogen deep placement was also reported in other studies of crop fields (Drury et al, 2006;Liu et al, 2006;Khalil et al, 2009). After basal nitrogen was deep placed, lower soil urease activity was observed under nitrogen deep placement treatments than under S treatment (Table 3), which may lead to less NH 4 + in the soils and floodwater from hydrolyzed nitrogen fertilizers under nitrogen deep placement treatments (Fig.…”
Section: Inhibition Of Nh 3 Volatilization Under Nitrogen Deep Placementsupporting
confidence: 84%
“…However, the USG overall retained more mineral N compared with the sPAT and UNI treatments. The findings signify that both the USG and urea amended with inhibitors (DCD/TZ and UNI) could effectively limit nitrification from 5-7 weeks, which is in accordance with laboratory (28,29) and field experiments (24). (29)).…”
Section: Inhibiting Nitrification: Influence Of Urea Granule Size Andsupporting
confidence: 87%
“…Khalil et al (28) examined the impact of USG point-placed at 2.5, 5 cm and 7.5 cm applied at 91.74 kg N ha -1 in a loess soil cropped to spring wheat on NO x emission. The maximum NO x emission peaked at 31 days after fertilization and thereby started to increase when NH 3 volatilization was declining (Fig.…”
Section: Decreasing No X Emissions: Effect Of Urea Granule Size and Umentioning
confidence: 99%
“…De toedieningsmethode is niet alleen bij vloeibare ureummeststoffen relevant maar ook bij korrels. Bij een toediening van ureumkorrels op een diepte van 2,5-, 5,0-, en 7,7-cm diep daalde de NH3 emissie 35 en 77% ten opzichte van de meest ondiepe plaatsing in een veldexperiment (Khalil et al, 2009 Basfoliar 36 extra,NTS 27 + 3 SO3,NTS 27 + 7,5 SO3,Plantacote start (ureaform npk),Plantosan (ureaform npk), Ureaform 38 N,Urean 28 N,Urean 30 N,Ureum 40% vlb,FertiFlow Plus,Powerstart Feed,Powerbasic Groei,Fertiflow Blue,Fertiflow Zomer 4 • De emissiefactor voor kalkloze landbouwgronden is 0%.…”
Section: Toedieningstechniekunclassified